Computational fluid dynamics simulations of spray tests in a multicompartment construction with an Eulerian–Lagrangian approach - Lu, Yazhe; Ran, Xu; Wei, Zonglan (Frontiers in Energy Research, 2024)
This paper investigates the effects of containment spray on hydrogen risk during a typical severe accident in a light water reactor (LWR): gas mixing and depressurization. Two spray tests are simulated, ST3_0 and ST3_1, conducted in the OECD/SETH-2 project frame. The tests were performed with different preconditions in two interconnected vessels of the PANDA facility, focusing on the breaking-up of stratified helium-rich layer and helium transport between the interconnected vessels under the conditions with or without heat and mass transfer. The simulations are performed using CFD code based on an Eulerian-Lagrangian approach, in which the dispersed droplets are tracked in a Lagrangian framework and the model of heat and mass transfer between droplets and gas is developed via UDFs (User Defined Functions). The simulation results show a reasonable agreement with test data and reproduce the main phenomena of the spray tests. The proposed approach is adequate to address similar problems while some discrepancies exist in the simulations. According to the discrepancies, some recommendations are drawn for the proposed approach to improve its accuracy.